1987
DOI: 10.1111/j.2044-835x.1987.tb01059.x
|View full text |Cite
|
Sign up to set email alerts
|

The emergence of the word length effect in young children: The effects of overt and covert rehearsal

Abstract: The purpose of this study was to examine the effect of training 5‐year‐olds to carry out both overt and covert rehearsal in a serial order recall task. As the superior recall for short words versus long words in adults is attributed to the use of verbal rehearsal, it was hypothesized that young children who do not normally show these effects would do so when trained to rehearse. Both overt and covert rehearsal were found to be equally effective in producing a word length effect, and these results were taken as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

1990
1990
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 11 publications
1
21
0
1
Order By: Relevance
“…Kanno & Ikeda, 2002;Vicari et al, 2004), a finding that at first sight might appear problematic for this account. However, many other studies have shown word length effects among individuals younger than 7 years of age, or functioning below the seven-year level (e.g., Hitch, Halliday, Dodd, & Littler, 1989;Hulme et al, 1984;Johnston, Johnson, & Gray, 1987). The fact that these word length effects are removed by probing for recall (Allick & Siegel, 1976;Balthazar, 2003;Henry, 1991;Turner, Henry, & Smith, 2000), thereby removing the need to produce a full spoken repetition of the item list, has led to the claim that word length effects at this level are due to output effects, with poorer recall of longer words reflecting the greater time to reproduce rather than rehearse these items (cf.…”
Section: Discussionmentioning
confidence: 98%
“…Kanno & Ikeda, 2002;Vicari et al, 2004), a finding that at first sight might appear problematic for this account. However, many other studies have shown word length effects among individuals younger than 7 years of age, or functioning below the seven-year level (e.g., Hitch, Halliday, Dodd, & Littler, 1989;Hulme et al, 1984;Johnston, Johnson, & Gray, 1987). The fact that these word length effects are removed by probing for recall (Allick & Siegel, 1976;Balthazar, 2003;Henry, 1991;Turner, Henry, & Smith, 2000), thereby removing the need to produce a full spoken repetition of the item list, has led to the claim that word length effects at this level are due to output effects, with poorer recall of longer words reflecting the greater time to reproduce rather than rehearse these items (cf.…”
Section: Discussionmentioning
confidence: 98%
“…This process was apparently not a more timeconsuming one for the long words; it may be that information has to be retrieved from the phonological store, and possibly also rehearsed, in order for word length effects to be shown at output. Even 5-year-olds, who do not spontaneously rehearse and do not normally show word length effects with full verbal recall, demonstrate better recall of short as opposed to long words when trained in covert verbal rehearsal of a series of pictures (Johnston, Johnson, & Gray, 1987). It seems likely that an instruction to rehearse for 5-year-olds encourages them to enter information into the phonological store, and that they retrieve that information from the store because they are instructed to rehearse prior to recall; the poor readers in the present investigation may have carried out only the first phase of this process (i.e., encoding without rehearsal or retrieval from the phonological store).…”
Section: Discussionmentioning
confidence: 99%
“…Prior evidence that subvocal rehearsal is a strategic process that develops in middle childhood is available from a variety ofsources (see Gathercole & Hitch, 1993), including training studies in which rehearsal-associated phenomena emerge following rehearsal training in young children (Johnson, Johnson, & Gray, 1987) and observational studies oflip movements during recall tasks with older children (Flavell et aI., 1966). There was indeed some evidence for developmental change across the 5-and 8-year-old age groups.…”
Section: Discussionmentioning
confidence: 99%